Hormonal replacement therapy in women addicted to the tobacco smoke - Paszkowski, Tomasz; Wrona, Wojciech (Menopause Review/Przegląd Menopauzalny, 2005)
The authors review epidemiology and pathophysiology of the peri- and postmenopausal women’s exposure to the tobacco smoke. The influence of tobacco smoking on the estrogen metabolism as well as on the efficacy and safety profile of the HRT is discussed in detail. According to the currently accepted opinions, in women with indications for HRT, the parenteral route of administration and the minimally effective doses of hormones should be used.